Systematic Review of Pharmacogenetics of Immunosuppressants in Heart Transplantation - Juan Eduardo Megías-Vericat; Tomás Palanques-Pastor; Mireya Fernández-Sánchez; Eduardo Guerrero-Hurtado; Mayte Gil-Candel; Antonio Solana-Altabella; Octavio Ballesta-López; María Centelles-Oria; Javier García-Pellicer; José Luis Poveda-Andrés (Cardiogenetics)
The standard immunosuppressive treatments in heart transplantation are calcineurin inhibitors, corticosteroids, and antimetabolite agents or inhibitors of the mammalian target of rapamycin. Pharmacogenetic studies show the impact on clinical course of genetic variability in genes that encode transporters, metabolizers, or molecular targets of immunosuppressants. The aim of this systematic review is to elucidate the role that pharmacogenetics of immunosuppressant drugs plays in clinical outcomes upon heart transplantation. PubMed, EMBASE, the Cochrane Central Register, and the Database of Abstracts of Reviews of Effects were searched without restrictions. The 64 studies analyzed followed these criteria: (1) were based on clinical data on heart transplantation patients; (2) analyzed the associations between polymorphisms and clinical response; (3) analyzed the impact of polymorphisms on immunosuppressant safety. CYP3A4/5 variants were associated with higher doses of tacrolimus, whereas POR*28 variants with lower doses—ABCB1, ABCC2, SLCO1B1, and SLC13A1—contribute to interindividual variability in drug absorption, distribution, and toxicity. An ABCC2 polymorphism (rs717620) was related to higher risk of graft rejection in pediatrics. Variations in HLA-G, TNF-α and TGF-β genes influence transplant rejection risk and immune response. Implementing pharmacogenetic screening of polymorphisms could enhance therapeutic outcomes by improving drug efficacy, reducing toxicity, and ultimately increasing heart graft survival rates. Strong evidence supports genotyping for CYP3A5 and TPMT, but further research is required for transporter genes and cytokine polymorphisms.